The Discovery Learning Activities of "Science is Fun" Program of Kompas TV to Teach English for Young Learners - Annahdhi Dzikri Fajriyah; Erly Wahyuni (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Discovery Learning Activities of "Science is Fun" Program of Kompas TV to Teach English for Young Learners